FUNGSI IDEASIONAL DALAM BAHASA KAILI: SEBUAH TINJAUAN LINGUISTIK SISTEMIK FUNGSIONAL (IDEATIONAL FUNCTION IN KAILI LANGUAGE: A SYSTEMIC FUNCTIONAL LINGUISTICS VIEW) - Darmawati Majid Rosni (Balai Bahasa Sulawesi Utara, 2018)
This paper aims to find the ideational functions in bahasa Kaili. Linguistics Systemic Function Halliday is used to find that Ideational Function. The data is collected through a library method, using reading and note taking techniques. Data were analyzed using a qualitative descriptive approach. The results of the analysis showed that in the mental process, there is only one participant in a clause, in the form of a human, who senses-thinks, feels-who always has consciousness. While in the material process, every participant is something, while in the mental process, concerning perceived, thoughtful, or accepted, the position of sense or sense is not only limited to certain semantic or grammatical categories but broader than the participants in the process material. In short, participants in mental processes are not just ‘something’ but, it can be facts. It is lead to one conclusion that in general, the structure of the Kaili and Indonesian language clauses is not quite different between each other.